Characterization and Pickering emulsifying ability of Adinandra nitida leaf polysaccharides - Yingxuan Zhou; Lu Bai; Sheng Geng; Benguo Liu (Food Chemistry: X, 2025)
Herein, Adinandra nitida leaf polysaccharides (ANPs) were isolated, identified, and used as a particle emulsifier to stabilize Pickering emulsions. ANP was identified as a polysaccharide with a weight-average molecular weight of 383.10 ± 8.57 kDa that was mainly composed of galacturonic acid (43.94 ± 3.63 mol%), arabinose (17.44 ± 1.06 mol%), glucose (8.53 ± 0.65 mol%), and rhamnose (4.88 ± 0.32 mol%). The main glycosidic linkages included t-Ara(f)-(1→, →4)-Gal(p)-(1→, and →4)-Gal(p)-UA-(1→, with molar percentage ratios of 8.97 %, 19.68 %, and 47.05 %, respectively. ANP possessed a reducing power and ABTS radical scavenging ability. ANP could also reduce the interfacial tension between medium-chain triglycerides (MCT) and water in a concentration-dependent manner, demonstrating its emulsifying role. When the addition amount (c) ≥ 3 %, ANP could stabilize the O/W-type MCT-based Pickering emulsion gel with an oil-phase volume fraction of 70 %, and c was proportional to mechanical parameters such as gel strength, macroscopic viscosity index, and elastic index.